Changes in The Commonwealth of Nations as an attempt to redefine an imperialistic heritage - Kwiatkowski, Bartosz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The aim of this article is to describe the changes that took place in the modern history of the Commonwealth of Nations, an international organization in which legal and political links between the Anglo-Saxon and the Oriental world are widely present. By examining the evolution of its institutions during and after the process of decolonization, the author captures crucial directions of those changes, their nature and also their meaning, which leads to interesting conclusions referring not only to the outcome of attempts to renounce the British imperialism in the internal structure of the Commonwealth, but also to those aspects of mentioned reforms that may be important in the future of the organization
Keywords: the Commonwealth; decolonization; international organizations